2003
DOI: 10.1194/jlr.m200252-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of hepatic lipogenic enzymes in an animal model of sedentariness

Abstract: The hindlimb-suspended rat was used as animal model to investigate the effects induced by immobilization of the skeletal muscle in the expression of the genes encoding hepatic lipogenic enzymes. Following a 14-day period of immobilization, rats were injected intraperitoneally with radioactive acetate, and the labeling of hepatic lipids and cholesterol was evaluated 15 min after the isotope injection. The incorporation of labeled acetate in lipids and cholesterol was almost three times higher in the liver of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…However, there appeared to be a trend ( p = 0.14) towards significance for mature SREBP-2 in the gastrocnemius muscle, with HU rats expressing lower levels. In a previous study investigating the liver of rats undergoing 14 days of HU, mature SREBP-2 expression was reported to be elevated in comparison to CC animals [28]. Those results, in combination with our data, present contrasting effects of HU on cholesterol metabolism in the liver and muscle.…”
Section: Discussionsupporting
confidence: 83%
“…However, there appeared to be a trend ( p = 0.14) towards significance for mature SREBP-2 in the gastrocnemius muscle, with HU rats expressing lower levels. In a previous study investigating the liver of rats undergoing 14 days of HU, mature SREBP-2 expression was reported to be elevated in comparison to CC animals [28]. Those results, in combination with our data, present contrasting effects of HU on cholesterol metabolism in the liver and muscle.…”
Section: Discussionsupporting
confidence: 83%
“…Frozen rat epididymal white adipose tissue (about 200 mg) was homogenized in 1 ml of 7% SDS. Aliquots of the homogenates con-taining 30 mg protein were mixed with sample buffer, boiled (1 min at 100°C) and centrifuged for 10 min at 3000´g as described (Vecchini et al, 2003). The relative abundance of precursor and mature SREBP-1 was evaluated by Western blot procedure as described above.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, large quantities of free fatty acids accumulate in the liver, causing hepatic lipogenesis. Simultaneously, free fatty acids in the blood also increase 8 , 9 ) . Kobayashi and colleagues reported that the %BF estimated by BIA is useful for the prediction of TC, LDL-C, and TG levels in Japanese men 10 ) .…”
Section: Discussionmentioning
confidence: 97%